Stan zachowania smalty w wybranych obrazach gdańskich: Antona Möllera (1563/5–1611), Hermanna Hana (1580–1627/8) i Isaaca van den Blocke (przed 1589 – po 1624) - Szmelter-Fausek, Bożena; Olszewska-Świetlik, Justyna (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2014)
The state of preservation of smalt in the selected Gdańsk paintings by Anton Möller (1563/5–1611), Hermann Han (1580–1627/8) and Isaac van den Blocke (before 1589 – after 1624) This works presents energy-dispersive X-ray microanalysis in a scanning electron microscope (SEM-EDS) and optical microscopy under ultraviolet light (VIS-UV) analysis of painting layer containing the blue pigment smalt of selected panel paintings by the Gdańsk artists of the 17th century Golden Age: Anton Möller, Isaac van den Blocke and Hermann Han. Application of SEM-EDS and VIS-UV methods allowed to analyze individual layers containing smalt and to determine the state of preservation of this pigment. The results helped to understand the process of deterioration of blue layer painted with smalt